2009
DOI: 10.1177/0959683609348850
|View full text |Cite
|
Sign up to set email alerts
|

Charcoal fragments of Alpine soils as an indicator of landscape evolution during the Holocene in Val di Sole (Trentino, Italy)

Abstract: Subalpine and Alpine soils in Val di Sole (Trentino, Italy) have been investigated in order to reconstruct vegetation changes and human impact during the Holocene period. Archaeological findings have demonstrated that Alpine sites have been populated since pre-historical times. Humans have had a great impact on the natural landscape evolution. One of the most-used tools has been fire. The use of fire has enabled the landscape to be cleared to provide new pastures for grazing and also to allow it to be used for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 55 publications
1
26
0
2
Order By: Relevance
“…However, taxonomic identification of macrocharcoal fragments suggest that Larix presence is continuously recorded during Holocene times at a higher altitude in the nearby Valle di Sol (up to 2200 m a.s.l. ; Trentino, Favilli et al, 2010). Larix presence has also been documented for the last millennia in Lake Tovel (1177 m a.s.l.…”
Section: S Joannin Et Al: Climate and Vegetation Changes During Thementioning
confidence: 97%
See 1 more Smart Citation
“…However, taxonomic identification of macrocharcoal fragments suggest that Larix presence is continuously recorded during Holocene times at a higher altitude in the nearby Valle di Sol (up to 2200 m a.s.l. ; Trentino, Favilli et al, 2010). Larix presence has also been documented for the last millennia in Lake Tovel (1177 m a.s.l.…”
Section: S Joannin Et Al: Climate and Vegetation Changes During Thementioning
confidence: 97%
“…1000 mm. Location of pollen sites discussed in the paper for the Alps and northern Italy -1: Lake Lavarone (Filippi et al, 2007); 2: Lake Lucone ; 3: Passo del Tonale (Gehrig, 1997); 4: Valle di Sol (Favilli et al, 2010); 5: Lake Tovel (Gottardini et al, 2004); 6: Palù di Sonico (Gehrig, 1997); 7: Pian di Gembro (Pini, 2002); 8: Totenmoos (Heiss et al, 2005); 9: Palughetto Cansiglio Plateau (Vescovi et al, 2007); 10: Lago di Fimon (Valsecchi et al, 2008); 11: Lago della Costa (Kaltenrieder et al, 2009(Kaltenrieder et al, , 2010; 12: Lago di Annone (Wick and Möhl, 2006); 13: Lej da San Murezzan (Gobet et al, 2003); 14: Lago Ragogna (Monegato et al, 2007); 15: Lago di Origlio (Tinner et al, 1999); 16: Balladrum (Hofstetter et al, 2006); 17: Piano ; 18: Gerzensee (Lotter et al, 2000); 19: Soppensee (Lotter, 1999); 20: Lobsigensee (Tinner and Vescovi, 2005); 21: Lago Piccolo di Avigliana ; 22: Lago del Greppo ; 23: Lago dell'Accesa (Drescher-Schneider et al, 2007). (c) Catchment area of Lake Ledro (dotted line).…”
Section: Study Areaunclassified
“…Several authors stressed the importance of increasing landscape heterogeneity also by means of prescribed fire (e.g., Moreira et al 2011). Given the important role that fire has played in fostering biodiversity in Italian ecosystems (Sereni 1981, Delogu & Cabiddu 2009, Conedera & Krebs 2010, Favilli et al 2010, there is much research potential on the effectiveness of PB for biodiversity conservation. Ascoli et al (2012) identified several EU Natura 2000 habitats (code Habitat Directive: 2240Directive: , 2270, in addition to marshlands dominated by Carex spp.…”
Section: Challenges Of Prescribed Burning In Italymentioning
confidence: 99%
“…In the Greco-Roman world, the use of fire was widespread in Mediterranean Italy (Susmel 1973) to create or regenerate pastures, fertilize fields, hunt, and control pests (Sereni 1981, Pyne 1982. Also in the Alps, between 6500 BC and 800 AD, slash and burn (debbio) was broadly used to open new pastures and agricultural fields (Ali et al 2005, Tinner et al 2005, Favilli et al 2010). However, starting from the late Middle Ages, the use of fire in northern Italy decreased (Conedera & Krebs 2010).…”
Section: Socio-cultural Issuesmentioning
confidence: 99%
“…(Merkli et al, 2009). This relatively short geomorphologic evolution directly influences the age of the soils, which started to form after the Last Glacial Maximun (LGM) (Egli et al, 2008;Favilli et al, 2010).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%